2015
DOI: 10.14740/wjon911w
|View full text |Cite
|
Sign up to set email alerts
|

Periampullary and Pancreatic Metastases of Renal Cell Carcinoma: An Underdiagnosed Event

Abstract: The National Cancer Institute reports high incidence of renal cell carcinoma (RCC) in the US compared to other regions. However, pancreatic and periampullary metastasis are uncommon when only 17% of the RCC cases metastasize overall. We herein present a case series of four patients with periampullary or pancreatic metastatic disease following complete resection of RCC, evaluating their occurrences and outcomes. We reviewed the cases of four male patients retrospectively, mean age 75 years (range 65 - 87) who h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
1
1
0
Order By: Relevance
“…Once surgical complications have been overcome, survival rate appears to be significantly higher in resected patients [20,29]. Results of our analysis present the justifiable possibility of curative-intended pancreas surgery in selected patients confirming data previously published by others.…”
Section: Discussionsupporting
confidence: 88%
“…Once surgical complications have been overcome, survival rate appears to be significantly higher in resected patients [20,29]. Results of our analysis present the justifiable possibility of curative-intended pancreas surgery in selected patients confirming data previously published by others.…”
Section: Discussionsupporting
confidence: 88%
“…A study reported two cases of metastatic RCC in the pancreas with mean time of metastasis of 41.5 months (0–108). Both patients were males aged 65 and 87 years [ 43 ]. RCC metastasis to colon can occur several years following curative resection of the primary tumor or it can occur soon after resection [ 44 ].…”
Section: Discussionmentioning
confidence: 99%